Epidemiology of Snake Bites Linked with the Antivenoms Production in Colombia 2008–2020: Produced Vials Do Not Meet the Needs (2022)
Introduction: Snakebite envenomation is a public health event of mandatory reporting in Colombia. It is considered a medical emergency in which the government must guarantee antivenom availability. We describe snakebite epidemiological figures in Colombia between 2008 and 2020 and correlate them with antivenom manufacturing figures to determine rate coverage and the need for antivenom. Methods: We performed an ecological study based on secondary official figures from the National Health Institute, the National Institute for Surveillance of Medicines and Foods, the National Administrative Department of Statistics and the Ministry of Health and Social Protection. Absolute and relative frequencies were calculated with 95% confidence intervals, position measurements, dispersion and central tendency. Results: Through our research, we revealed that in the last 13 years (2008–2020), there were an average of 4467 annual snakebite envenomation cases affecting all the departments in Colombia. Antioquia reported the highest number of snakebites with 647 (95% CI 588–706) cases per year. The population incidence per 100,000 inhabitants was 9.5; the highest rates were found in Vaupés at 116.1 and Guaviare at 79.24. During the last seven years (2014–2020) Colombia produced an average of 21,104 antivenom vials per year, while the annual demand for antivenom is estimated at 54,440 units needed to guarantee access. Discussion: Colombia does not produce sufficient vials to cover their needs, and this is why only 74.4% of accidents (out of the 92% not classified as dry bites) were treated, and even 9.7% of the severe accidents did not receive the specific treatment (8% of the victims were classified as dry bites). Figures support the regular antivenom shortages declared by the Ministry of Health and Social Protection in the last 13 years (11 health emergency declarations). New efforts are needed to: 1) boost the production of GMP-based high-quality antivenom, that covers the national needs and is made availability, 2) a better estimation method to calculate the need for antivenom in Colombia, and 3) implementation of production-distribution chains guaranteeing access in remote communities.